PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 188 PEKANBARU - Iswari, Sufitri Indah; Witri, Gustimal; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is caused by low study outcome mathematic lesson student class fifth grade students state elementary school 188 Pekanbaru. The purpose of this research is to improve learning outcomes subject Mathematic fifth grade using Contextual Teaching and Learning Approach. Object of this research is student class fifth grade amount 34 person. Metode of this research using Classroom Action Research (CAR),was carried out in two cycle. The result of research mathematic learning outcomes is increase. Activities of teacher in the first meeting of first cycle of the percentage 75%, the second meeting of first cycle had become 84,14% . Furthermore, the first meeting of the second cycle activity score of 89,28% of teacher increased, the second meeting increased to 92,85%. The result of analysis student activity in the first cycle to 71,42%, 75% in the second meeting increased the student already understand this cycle of learning activity with Contextual Teaching and Learning (CTL) approach. The second cycle student activity increased 82,14%. At the second meeting increased to 89,28%.. The results showed that the average value of learning outcomes mathematic subjects in the basic score is 71,02 and 76,17 in the first cycle, and the second cycle get 80,58 score. Based on the results of this study is concluded that the Contextual Teaching and Learning approach can improve learning outcomes Mathematic subject of fifth grade students state elementary school 188 Pekanbaru.Key Words: Contextual Teaching and Learning Approach (CTL) and Mathematiclearning outcomes